IR-imaging and non-destructive loss analysis on thin film solar modules and cells - Adams, Jens; Fecher, Frank W.; Hoga, Felix; Vetter, Andreas; Buerhop, Claudia; Brabec, Christoph (Proceedings of SPIE - The International Society for Optical Engineering, 2014)
CIGS thin film solar modules, despite their high efficiency, may contain three different kinds of macroscopic defects referred to as bulk defects, interface defects and interconnect defects. These occur due to the film's sensitivity to inhomogeneities during the manufacturing process and decreasing the electrical power output from a cell or module. In this study, we present infrared (IR) imaging and contactless loss analyses of defects contained in commercially manufactured thin film solar modules. We investigated different relations between the emitted IR-signal (using illuminated lock-in thermography ILIT) and the respective open circuit cell voltage (Voc) as well as the maximum power point (Pmpp). A simulation study, using the 2D finite element method (FEM), provides a deeper understanding as to the impact on electrical performance when defects are present on the cell or module.
Keywords: 2D finite element method; CIGS thin film technology; Contactless; Defects; ILIT; Lock in thermography; Open circuit voltage